The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1182/blood.v128.22.4052.4052
|View full text |Cite
|
Sign up to set email alerts
|

Safety Data from a First-in-Human Phase 1 Trial of NKG2D Chimeric Antigen Receptor-T Cells in AML/MDS and Multiple Myeloma

Abstract: Introduction: Conventional CAR-T cells express a single chain antibody variable fragment that restricts recognition to one tumor antigen and a limited set of cancers. This study employs a novel CAR fusing full-length human NKG2D with the CD3z signaling domain. In autologous transduced CM-CS1 T cells, NKG2D CAR receives endogenous costimulation via DAP10 to target multiple NKG2D-ligands that are upregulated in solid and hematologic malignancies but absent or poorly expressed on healthy tissues. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The results showed that 9 subjects treated in the first 3 cohorts completed their 28-day evaluation period without any DLTs. It is worth mentioning that there was no case of cell-related neurotoxicity, cytokine release syndrome (CRS), autoimmunity or CAR T cell-related death during treatment [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 9 subjects treated in the first 3 cohorts completed their 28-day evaluation period without any DLTs. It is worth mentioning that there was no case of cell-related neurotoxicity, cytokine release syndrome (CRS), autoimmunity or CAR T cell-related death during treatment [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common adverse event was CRS (90% of the patients), including 14% grade 3/4 cases. Ongoing studies are investigating several other potential targets on MM plasma cell surface (196), including CD44v6 (197), Lewis Y (198), NKG2D ligands (199), CD229 (200), and integrin β7 (201). Selected clinical trial results in MM are summarized in Table 3.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…CAR‐T cells are also being investigated for use in generation of immune tolerance with solid organ transplant, autoimmune diseases (1 open CAR trial in lupus NCT03030976), and for infectious diseases . In conclusion, CAR T cell therapies targeting antigens and diseases beyond CD19 and B cell malignancies, respectively, have a bright future and are only beginning to emerge …”
Section: Hodgkin's Lymphomamentioning
confidence: 99%